Predictive Validity of UTME on First-Year Chemistry Students’ CGPA in Universities in South-East, Nigeria - Anselem Abonyi Ugwuanyi; Uzoamaka Pet Egbukwu; Monisade Folasade Aderanti; Calister Chinwe Eze; Blessing Adanu-Ogbole; Chukwuka Constance Uju (Scientia Publica Media, 2026)
The predictive validity of the Unified Tertiary Matriculation Examination (UTME) results on the first-year cumulative grade point average (CGPA) of chemistry education students in South-East Nigerian universities was investigated in this study. The study specifically examined whether gender and school type affect the association between UTME scores and students’ academic success. Three research questions and three hypotheses served as the investigation’s compass. The study design used was a correlational survey. In 2024–2025, 404 students (137 men and 267 women) were accepted into nine public institutions. Of these, 175 students (48 men and 127 women) were chosen at random from four universities. Students’ UTME scores, gender, school type, and first-year CGPA were gathered from institutional records using a structured proforma. Regression analysis, the t-test, and the Hayes macro process were used to analyze the data at the significance level of 0.05. The results showed a weakly positive correlation between first-year CGPA and UTME scores, with UTME making a negligible contribution to the variation in students’ academic achievement. UTME scores were not statistically significant predictors of first-year CGPA, according to the regression analysis. Additionally, there was no significant moderating effect of gender or kind of school on the association between academic achievement and UTME scores. The study comes to the conclusion that students’ academic progress in chemistry instruction cannot be predicted by UTME scores alone. It is advised that universities implement extra screening procedures to enhance admissions decisions and that admission authorities examine the UTME framework to better reflect the competencies needed for university education.